2020
DOI: 10.1097/brs.0000000000003303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Topography and Chemistry on Polyether-Ether-Ketone (PEEK) and Titanium Osseointegration

Abstract: Study Design. An in vivo study examining the functional osseointegration of smooth, rough, and porous surface topographies presenting polyether-ether-ketone (PEEK) or titanium surface chemistry. Objective. To investigate the effects of surface topography and surface chemistry on implant osseointegration. Summary of Background Data. Interbody fusion devices have been used for decades to facilitate fusion acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…If 3D printed roughness does in fact aid in implant fixation, artificial roughness will be designed on implant surfaces opposed to bone to increase early fixation at the bone‐implant interface. In addition, it is well known that porosity enhances osseointegration in metal implants 37 42 and recent work has shown that porosity is a larger factor in controlling osseointegration versus surface roughness alone 43,44 . Osseous integration remains a challenging problem in orthopedic implants likely requiring a multifaceted solution.…”
Section: Discussionmentioning
confidence: 99%
“…If 3D printed roughness does in fact aid in implant fixation, artificial roughness will be designed on implant surfaces opposed to bone to increase early fixation at the bone‐implant interface. In addition, it is well known that porosity enhances osseointegration in metal implants 37 42 and recent work has shown that porosity is a larger factor in controlling osseointegration versus surface roughness alone 43,44 . Osseous integration remains a challenging problem in orthopedic implants likely requiring a multifaceted solution.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to rough surfaces, porous PEEK surfaces exhibit increased osteoblastic differentiation and bonding strength with bone (Torstrick et al, 2018(Torstrick et al, , 2020. Numerous techniques have been applied to develop porous structures on the PEEK surface, including sulfonation, melt extrusion, porogen templating, and PIII technique (Zhao et al, 2013;Lu et al, 2014;Evans et al, 2015;Torstrick et al, 2016;Hieda et al, 2017;Yabutsuka et al, 2017;Wu et al, 2018;Yuan et al, 2018;Conrad and Roeder, 2020;Swaminathan et al, 2020;Wan et al, 2020).…”
Section: Modifications Of the Porous Structurementioning
confidence: 99%
“…Indeed, the stable chemical structure of PEEK makes it innately inert and keeps it from binding to bone directly, resulting in inferior osseointegration, which greatly hinders its further clinical application in the field of bone repair. 4,[7][8][9] Thus far, various surface modification techniques have been developed to improve the bioactivity of PEEK, such as thermal plasma spray, 10 cold spray, 11 spin coating, 12 chemical deposition, 13 sputtering, 14,15 ion beam assisted deposition, 16 laserassisted biomimetic process 17 and microwave assisted coating. 18 The main purpose is to induce calcium phosphate (Ca-P) coating on the PEEK surfaces, which can not only improve the osseointegration of the material but even endow it with excellent osteoconduction.…”
Section: Introductionmentioning
confidence: 99%